Ecoliterate : how educators are cultivating emotional, social, and ecological intelligence - Goleman, Daniel; Bennett, Lisa, 1959-; Barlow, Zenobia (San Francisco, CA : Jossey-Bass, 2012)
"A new integration of Goleman's emotional, social, and ecological intelligenceThis book portrays inspiring educators, activists, and students who embody a new integration of emotional, social, and ecological intelligence--or what the authors refer to as engaged ecoliteracy. It builds on the success of bestselling author Daniel Goleman's emotional and social learning, and shows how educators are extending the cultivation of these essential dimensions of human intelligence to include knowledge of and empathy for all living systems. With stories that range from the Arctic to Appalachia and New York to New Orleans it illustrates dynamic education and engagement about some of the most important ecological issues of the day, from oil and coal to food and water. It also features a comprehensive professional development guide and the five processes of engaged ecoliteracy. Daniel Goleman is author of several New York Times and Wall Street Journal bestseller titles: Emotional Intelligence, Social Intelligence, Primal Leadership, Vital Lies, and Ecological Intelligence Filled with illustrative examples of schools that have successfully created a "green culture" Includes a professional development guide to use in individual and group settings"--
Machine generated contents note: INTRODUCTION: From Breakdown to BreakthroughWhy We Need a New Ecological SensibilityMaking the ConnectionsFrom Emotional to Ecological IntelligencePutting the Pieces TogetherBeyond Our Collective Blind SpotBenefitting Academic and Ecological Well-beingThe Five Practices of Emotionally and Socially Engaged EcoliteracySTORIES FROM THE FIELDPART ONE STANDING STRONG ON A COAL MOUNTAIN1 Lessons from a Coal Miner's DaughterTeri Blanton and Wendell Berry, KentuckySidebar: How to Mine a MountainSidebar: Why Can't We Go Out and Play, Daddy?Sidebar: Deconstructing the Meaning of "Cheap"2 Taking a Power TripSpartanburg Day School, South CarolinaSidebar: What's My Connection?Sidebar: The Last MountainSidebar: Wendell Berry's Eight QuestionsPART TWO FROM ANGER TO ACTION IN OIL COUNTRY3 The Heart of the CaribouSarah James, Arctic Village, AlaskaSidebar: Top Ten Oil ProducersSidebar: United States Is Number One in Oil Consumption4 Beyond WhiningKids Rethink New Orleans SchoolsSidebar: The Many Uses of OilSidebar: Where's the Oil?PART THREE SHARED WATER: MOVING BEYOND BOUNDARIES5 Water Wars and PeaceAaron Wolf, Mediator and Oregon State University ProfessorSidebar: Your Number One Use of Water at Home (It's Not What You Think)Sidebar: Ocean Water in a Glass?Sidebar: The Resilience of Water6 From Restoration to ResilienceStudents and Teachers Restore a Watershed, Northern CaliforniaSidebar: The Rise of Dead ZonesSidebar: Freshwater BluesSidebar: The New Face of Water PollutionPART FOUR NOURISHING COMMUNITIES WITH FOOD7 Changing a Food System, One Seed at a TimeLa Semilla Food Center, Anthony, New MexicoSidebar: Test Your "Food IQ"Sidebar: How to Feed Nine Billion8 Forging the Food Justice PathTony Smith, Superintendent of Schools, Oakland, CaliforniaSidebar: The Rise of School Food ReformSidebar: Rethinking School LunchSidebar: The Curriculum ConnectionPROFESSIONAL DEVELOPMENT STRATEGIES9 Cultivating Ecoliterate Learning CommunitiesGuidelines for Engaging ColleaguesSidebar: Using Circles to Cultivate Deep ListeningSidebar: Transformation in the Classroom10 Reflection and PracticeConversation Prompts for Getting StartedSidebar: Going on a Virtual DiveSidebar: Professional Development Sample AgendasCONCLUSION: Hands-on HopeEndnotesSourcesIndexAbout the AuthorsAbout the Center for Ecoliteracy
Includes index.
Keywords: Environmental education -- United States; Emotional intelligence -- Study and teaching -- United States; Social intelligence -- Study and teaching -- United States; EDUCATION / General